2013
DOI: 10.3329/bjch.v36i3.14274
|View full text |Cite
|
Sign up to set email alerts
|

Serum Calcium Status of Neonates with Seizure in a Tertiary Care Hospital

Abstract: Background: Seizure is a common neurological disorder in neonatal age group. Primary metabolic derangement is one of the common reason behind this convulsion during this period. Among metabolic abnormalities, hypocalcaemia is most common followed by hypoglycemia and hypomagnesaemia.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
6
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(9 citation statements)
references
References 8 publications
3
6
0
Order By: Relevance
“…This is in contrast to present and previous studies. 6,8,13 In present study, 11% of controls were suffering from hypocalcemia that is comparable to the Baten et al 13 that noted in 20% of control. In present study, the duration of <5 minutes seizures in controls were noted in 7 and in cases in 73.…”
Section: Discussionsupporting
confidence: 88%
See 3 more Smart Citations
“…This is in contrast to present and previous studies. 6,8,13 In present study, 11% of controls were suffering from hypocalcemia that is comparable to the Baten et al 13 that noted in 20% of control. In present study, the duration of <5 minutes seizures in controls were noted in 7 and in cases in 73.…”
Section: Discussionsupporting
confidence: 88%
“…This frequency is very small and is inconsistent with present and previous studies. 8,13 Approximately, 94 controls showed convulsion frequency of <1 while 84 cases showed ≥4 convulsions (p=0.0001). Nature of convulsions was; focal in 37%, subtle in 31% and mixed in 32% of cases.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Local data on the relationship between calcium or vitamin D and other outcomes in young children are limited. Baten et al 85 conducted a case–control study of 50 healthy neonates and 50 with recent idiopathic convulsions in Dhaka, measured serum calcium, and determined 60% of cases and 20% of controls were hypocalcemic (mean serum concentration was 6.48 vs 8.28 mg/dL, respectively). In a case–control study of 87 hypocalcaemic and 246 normocalcaemic severely malnourished children admitted to a Dhaka ICU, Chisti et al 86 found a 26% prevalence of hypocalcaemia; acute watery diarrhea, convulsions, and lethargy were independent predictors of hypocalcaemia in this population.…”
Section: Consequencesmentioning
confidence: 99%